"Bring yourself to work": rewriting the feeling rules in "personalized" social work. Issue 3 (18th September 2019) - Whitaker, Emilie Morwenna
Abstract : Purpose: The purpose of this paper is to explore how feeling rules are constructed, experienced and contested within personalised social work practice. It considers how organisations seek to shape practitioners towards certain forms of emotional display in increasingly market-oriented conditions. It contributes to our understanding of the place of "backstage" emotional labour in seeking to shape and direct social work practice. Design/methodology/approach: A single immersive ethnographic case study of an English social work department was undertaken over a period of six months. Findings: This paper reveals embedded tensions that emerge when practitioners are caught between traditional bureaucratic function, the incursions of the market and feeling rules of relatability, commitment and creativity. Originality/value: This paper contributes to the scant literature on frontline experiences of personalisation in children's services and the importance of "backstage" emotional labour for shaping and directing social work practice. Importantly, it considers the complexity of emotional labour within an organisational context, which is neither fully marketised, nor fully welfarised, a position many welfare organisations now find themselves in.